تحسين موثوقية الاتصالات في شبكات ال Multicast باستخدام تبديل مفاتيح التشفير - حجازية, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
With the increasing demand for communications in Multicast networks and the rapid and changing evolution of these networks, it has been necessary to achieve high reliability of these connections, meaning that the members authorized to use this service are only able to access any content related to the communications of this group Therefore, the best solution was to encrypt the group broadcast data from the sender with the shared group key with all authorized members so that symmetric encryption prevents other users from accessing the content to achieve this goal, a technique called RE-KEYING was used in the research. This is done after each user has joined the group to prevent him from obtaining old information and after each user's departure to prevent him from accessing future information. This research contributes to the development of the technique of using RE-KEYING encryption technology to ensure and improve the reliability of communications in multicast networks and to show how to distribute and exchange the key among the members of the group and then to indicate the meaning of confidentiality and reliability in these networks مع تزايد الطلب الكبير على الاتصالات في شبكات البث المجموعاتي Multicast إضافة إلى التطور المتسارع والمتغير في هيكلية هذه الشبكات ، كان لابد من العمل على تحقيق موثوقية عالية لهذه الاتصالات ، بمعنى أن الأعضاء المخولين باستخدام هذه الخدمة قادرين فقط على الوصول إلى أي محتوى يخص اتصالات هذه المجموعة و لذلك كان الحل الأمثل هو تشفير بيانات البث المجموعاتي من المرسل بمفتاح المجموعة المشترك مع كل الأعضاء المخولين وبذلك التشفير المتناظر يمنع المستخدمين الآخرين من الوصول إلى المحتوى .و لتحقيق الغاية المطلوبة تم في البحث استخدام تقنية تدعى ب RE-KEYING ، أي تغيير المفتاح حيث يجب أن تُنجز هذه العملية بعد كل انضمام المستخدم الى المجموعة وذلك لمنعه من الحصول على معلومات قديمة وبعد كل مغادرة المستخدم وذلك لمنعه من الوصول إلى المعلومات المستقبلية[1,3] هذا البحث يساهم في تطوير أسلوب استخدام تقنية مفاتيح التشفير RE-KEYING لضمان وتحسين الموثوقية للاتصالات في شبكات البث المجموعاتي ال multicast مع تبيان كيفية توزيع وتبادل المفتاح بين أعضاء المجموعة ومن ثم تبيان معنى السرية والموثوقية في هذه الشبكات